GENETIC STUDIES OF SEED OIL AND PROTEIN PERCENTAGE IN Gossypium hirsutum L. - Murtaza, Naveed; Khan, Azhar Ali; Qayyum, Abdul (Journal of Research (Science), 2002)
Pattern of inheritance were examined for seed oil and protein percentage in 8 x 8 diallel cross analysis of upland cotton. Additive (D) and non-additive (H1 and H2) gene effects were present for both the traits. Dominance component (H1), however, was higher than the additive (D) component for both the characters. Asymmetrical distributions of dominant and recessive genes in the parents were observed for both the characters. Low to high estimates of narrow sense heritability was obtained for oil and protein percentage.